Reflections on the introduction to basketball through education rules - Vizcaíno Domínguez, Celestina; Sáenz-López Buñuel, Pedro; Rebollo González, José Antonio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2012)
Traditionally, the process of teaching and learning has come from the election, by the coach, of those technical and tactical contents considered appropriate depending on the category, and from this point on, has turned all the planning, leaving out the teaching of the rules to an occasional appearance, without a prior organization in most of the cases. If we consider that the rules of game are a key element for the game, we could start to help the player to learn the technical and tactical means from the knowledge of the rules of game. With this study, we try to understand the current state of regulations in the stage of Minibasket and understand what is the role of rules in the introduction to basketball and how to sequence the teaching and learning of technical and tactical means from the rules.